Pengaruh Lafaz NÄá¹£ al-â€˜á¾¹m (Umum) dan NÄá¹£ al-KhÄá¹£ (Khusus) pada Ijtihad Para Ulama - Mahmuddin, Ronny (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2016)
Moslem scholars are the prophetsâ€™ heir. There have been the Islam treasuries which they have bequeathed for Islam generations. That it cannot be denied happens diï¬€erence of their ijtihÄd in doing istinbÄá¹ the law of a problem, but their diï¬€erences are based on argumentation, although there is the better opinion than others (rÄjiá¸¥). It is related with that, the existence of the Common and special texts in al-Qurâ€™Än and Hadith is one of factors inï¬‚uencing the moslem scholarsâ€™ ijtihÄd in doing istinbÄá¹ (to decide) the law of a problem. Keyword : Lafaz, NÄá¹£, Ijtih á¹£ Äd.